PERILAKU AUS DAN KOROSI LAPISAN BAJA TAHAN KARAT 420 DENGAN METODE ELECTRIC ARC SPRAY - Rina Lusiani; Aris Munandar; Erny Listijorini; Iman Saefuloh; Shofiatul Ula; Sunardi Sunardi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Thermal spray coating is a material protection process by depositing the coating material on the substrate material. Process parameters such as spray-off distance, surface roughness, and substrate preheat temperature, spray time, voltage, and arc current greatly influence the mechanical and tribological behavior. Selection of appropriate process parameters and coating materials must be carried out to obtain a coating that meets the design requirements. The coating method used is electric arc spray with parameters: spray-off distance of 200 mm, compressor air pressure of 7 bar, voltage of 32 volts, and layer thickness of 1 mm. At the same time, the independent variables are arc currents: 159, 185, and 299 amperes. The substrate material is AISI 1045 steel, PMET 885 intermediate material, and PMET 720 coating material. The tests carried out were observing the microstructure, hardness, wear rate, and corrosion rate. This research shows that the higher the arc current, the better the coating quality. At an arc current of 229 amperes, it is known that the hardness, the wear rate, and the corrosion rate are 398.10 VHN, 8.96 x 10-8 gram/mm2.s, and 0.8911 mpy, respectively. This research's contribution is to provide a reference on the influence of the arc current of the electrical arc spray coating process on the tribological behavior of the surface layer so that suitable for the desired application.